Transnational Dis-locations and Re-emplacements: Finding Home in NoViolet Bulawayoâ€™s â€œWe Need New Namesâ€ - Phepheng, Maruping (WritingThreeSixty, 2018)
Drawing on the novel We Need New Names (2013) by expatriate Zimbabwean author NoViolet Bulawayo, this paper examines the altering impact the host-land can have on the diasporic, and how factors prevailing in the new spatial setting can be constitutive of new identity and the reconstruction of memory. Central to this paper are themes of (un)belonging, of inclusion and exclusion, of assimilation and re-emplacement, of dis-locations and home in the diaspora. Scholars of the novel have suggested that We Need New Names is not a migrant novel in the traditional sense of the term: instead of focusing uniquely on the dislocated condition, the novel intertwines specific Southern African localities with the American diaspora. Bulawayo depicts harsh conditions at home - fractured families, disease, hunger, and death - rendering mobility a necessity. The novelâ€™s treatment of mobility is not restricted to migration, but can be understood in a broad way to pertain to locality in terms of peopleâ€™s dreams and hopes of a home elsewhere. Also examined is the use of online and cyberspace communication between host-land and homeland. The paper attempts to establish whether this form of communication has the effect of collapsing divisive borders. Centrally, this paper examines the transformation of memory and identity in the diaspora through the lens of space and place.